Evaluation of the level of physical activity, anxiety and depression symptoms in undergraduate students of the Physical Education course during social isolation (Research, Society and Development, 2023)
The goal of this study, carried out through quantitative social research, was to evaluate the level of physical activity, anxiety and depression symptoms in undergraduate students of the Physical Education course at Universidade Federal de Goiás during the period of social isolation caused by the COVID-19 pandemic. Furthermore, other factors pottentially associated with the outcomes analyzed were surveyed. Forty-one college students of both genders (23.9 ± 4.7 years old; 169.9 ± 9.7 cm; 71 ± 16.1 kg) participated in the study. Information on the level of physical activity (PA), state anxiety (SA), trait anxiety (TA), and depression symptoms (DS) were collected. Most of the college students were classified as active (36.6%) and very active (29.3%) (205.7 ± 331.27 MET daily; of 1440.0 ± 2318 MET weekly). Approximately, 53.7% and 56.1% of the subjects had high scores for SA and AT, respectively. Approximately 39% of subjects presented moderate or severe DS. Associations were identified between SA and DS (r= 0.84; p